VD_FINDINFO Pron / 2011 / 45 vom 21. April 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, DEMANDEACTION EN JUSTICE, CONCLUSIONS | 141 al. 1 CPC, 17 al. 1 CPC, 17 al. 3 CPC, 18 CPC, 262 CPC, 264 al. 1 CPC, 265 CPC